Prevalence of burnout syndrome in Brazilian anesthesiologists during the COVID-19 pandemic: A cross-sectional survey. - Liana M T A Azi; Thaiane S Ferreira; Thiago Cerqueira-Silva; Luis A S Diego; Marcos A C Albuquerque; Matheus L Azi (PLoS ONE)
Background Burnout syndrome, one of the consequences of chronic exposure to stressful, is more prevalent among physicians compared to the general population. Anesthesiology, alongside high-stress specialties such as emergency medicine and surgery, is particularly susceptible to this condition. During the COVID-19 pandemic, anesthesiologists were often on the front lines, potentially exacerbating burnout. This study aimed to assess the prevalence of burnout syndrome among Brazilian anesthesiologists during the pandemic. Methods A cross-sectional analytical observational study was conducted with all members of the Brazilian Society of Anesthesiology (SBA). Data were collected via sociodemographic questionnaires and the Maslach Burnout Inventory (MBI), disseminated by email. Results Burnout syndrome was identified in 19.6% (n = 213) of respondents, while 56.5% (n = 613) were at high risk for developing burnout. Having considered quitting the specialty was the variable most strongly associated with the prevalence of burnout syndrome and the high risk of burnout. As a protective factor, dedicating more time to leisure (over 5 hours per week) was related to a lower occurrence of burnout syndrome and its risk. Conclusion Burnout syndrome is highly prevalent among Brazilian anesthesiologists and residents. Target strategies to mitigate burnout should be implemented by healthcare institutions, professional organizations, and government bodies.